Promoting Senior High School Students’ Acquisition of Science Process Skills in Biology Using Experiential Learning Approach in Anambra State, Nigeria - I.S, Nwuba; A.M, Osuafor; O.S, Egwu; O.F, Awosika (Asian Journal of Interdisciplinary Research, 2022)
The study explored the impact of experiential learning approach (ELA) on acquisition of science process skills (SPS) by biology college students. The research design is quasi-experimental research, adopting the non-randomized manipulated group of 2x2 factorial research design. 58 (22 males and 36 females) Senior High School II students in Awka Education Zone, obtained with multi-leveled sampling method made up the sample size. The sampled students who were in two separately grouped classes were randomly assigned to experimental and control groups using a flip of a coin. A Biology Science Process Skills Acquisition Test (BSPSAT) with 0.71 reliability coefficient ascertained with Kuder Richardson formula 20 was used to collect data. Average Mean and Standard deviation were adopted to describe the research questions and Analysis of Covariance to test the null hypotheses. The findings showed that ELA promoted students’ acquisition of SPS in biology more than the Conventional Lecture Method. Gender alone as well as its interaction effect with the teaching methods had no significant effect on acquisition of SPS by students in biology. The study resolved that ELA is an activity-based approach that engages students actively throughout the learning process, hence promoting their acquisition of SPS. In line with the findings, the study advised that biology teachers should adopt ELA in schools to promote students’ acquisition of SPS.